Kepemimpinan Kepala Sekolah dalam Meningkatkan Disiplin Kerja Guru di SMP Negeri 2 Kotamobagu - Fidya Tampoy; Sukarman Kamuli; Ariyanto Nggilu (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Teacher work discipline is a cornerstone of instructional effectiveness and the enhancement of educational quality. However, at SMP Negeri 2 Kotamobagu, a decline in motivation was observed among teachers nearing retirement, alongside a "comfort zone" phenomenon among tenured teachers, necessitating specific interventions by the school principal. This study aims to analyze the principal's leadership in improving teacher work discipline and to describe the level of work discipline among teachers at the school. A qualitative approach with a descriptive method was employed. Data were collected through observation, in-depth interviews, and documentation, involving the principal and teachers as informants. Data validity was verified using source and technique triangulation, followed by analysis involving data reduction, data presentation, and conclusion drawing. The results indicate that the level of teacher work discipline is generally good demonstrated by punctuality and professional responsibility despite fluctuations within certain teacher groups. The study’s novelty lies in highlighting that shifting from regulation-based compliance to authentic professional awareness requires a humanistic and segmented leadership approach. In conclusion, a combination of affective role-modeling, dialogic guidance, and educational supervision constitutes the most effective strategy for addressing motivational stagnation and fostering teacher discipline. The practical implications of this study emphasize the need for principals to adopt an integrative-persuasive leadership style tailored to the teachers' psychological career stages to sustain a professional work culture.